The Effect Of Discipline And Work Environment On Employee Performance In The Warehouse Division At PT. Nusantara Logistics Group Tangerang - Gandung, Muhammad; Sunarsi, Denok; Suwanto, Suwanto (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to analyze and determine the influence of work discipline and work environment on employee performance in the Warehouse Division at PT Nusantara Logistics Group Tangerang. The background of this study is based on the important role of human resources in achieving operational effectiveness and efficiency of logistics companies, which are highly dependent on employee punctuality, accuracy, and responsibility. Strong work discipline and a conducive work environment are believed to contribute positively to improving individual and team performance within an organization. This study uses a quantitative descriptive method with a survey approach. The study population is all 60 employees of the Warehouse Division of PT Nusantara Logistics Group Tangerang, and because the number is relatively small, a census sampling technique is used where the entire population is used as respondents. The research instrument is a questionnaire with a five-point Likert scale covering three main variables, namely work discipline (X?), work environment (X?), and employee performance (Y). The collected data are then analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, as well as t-tests and F-tests to test partial and simultaneous hypotheses. The results of the study indicate that work discipline has a positive and significant effect on employee performance, with a calculated t value of 3.982 > t table 2.001 and a coefficient of determination (R²) of 21.5%. This means that increasing discipline in the aspects of attendance, responsibility, and compliance with regulations makes a significant contribution to improving individual performance. Furthermore, the work environment also has a significant effect on employee performance, with a calculated t value of 3.352 > t table 2.001 and a coefficient of determination of 16.2%. A comfortable, safe work environment, as well as good social relations between coworkers and superiors, have been shown to increase employee motivation and productivity. Simultaneously, the results of the F test show that discipline and the work environment together have a significant effect on employee performance, with a calculated F value of 7.903 > F table 2.77 and a simultaneous coefficient of determination of 21.7%. This means that these two variables collectively explain about one-fifth of the variation in employee performance, while the remaining 78.3% is influenced by other factors such as work motivation, leadership style, compensation system, and organizational culture that are not discussed in this study.